Biodegradable polymer hydrogel‐based tissue adhesives: A review. Issue 4 (3rd August 2021) - Zhang, Xin; Jiang, Yanan; Han, Lu; Lu, Xiong
Abstract: Tissue‐adhesive materials are emerging biomaterials with potential applications in wound healing patches, tissue sealants, and haemostat materials. Tissue adhesives based on synthetic polymers generally have good adhesion but are not biodegradable. However, the long‐term presence of non‐biodegradable adhesives in the body can cause secondary harm to the patient. An ideal tissue adhesive should meet the following requirements: good adhesiveness, biodegradability, low cytotoxicity, and minimal inflammatory response. Natural polymers with inherent biodegradation and biocompatibility show great potentials in biomedical engineering, and the development of tissue adhesives based on natural polymers has become a hot topic in biomaterials science. This review systematically summarises the latest progresses in biodegradable tissue adhesives based on natural polymers, such as chitosan, hyaluronic acid, alginate, gelatin, dextran, and cellulose. Methods for preparing natural polymer tissue adhesives are summarised and their advantages and disadvantages are discussed. Finally, potential trends in the future direction of biodegradable tissue adhesives are discussed.